2016
DOI: 10.5539/jel.v5n2p73
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Success in Introductory Programming: A Study with Middle School Students

Abstract: <p>The demand for computing professionals in the workplace has led to increased attention to computer science education, and introductory computer science courses have been introduced at different levels of education. This study investigated the relationship between gender, academic performance in non-programming subjects, and programming learning performance among middle school students with no prior programming experience who took an introductory programming course. We found that girls performed as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 40 publications
1
21
1
4
Order By: Relevance
“…Students from all engineering disciplines take introductory programming and there is a wide range of abilities of the students coming in the class. Some may have studied some programming in high school or learned it on their own [6]. Others may have no exposure to programming at all and that can be rather intimidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students from all engineering disciplines take introductory programming and there is a wide range of abilities of the students coming in the class. Some may have studied some programming in high school or learned it on their own [6]. Others may have no exposure to programming at all and that can be rather intimidated.…”
Section: Discussionmentioning
confidence: 99%
“…The exact number may be different for engineering students but the fact of the matter is that a significant number of engineering students struggle and/or do not do well in their introductory programming class. Factors in doing well no doubt include prior preparation [6][9] [10] however the result of not doing well in any class can be due other issues such as: not paying attention, not doing the assignments, not keeping up with the work, etc. Like missing the first five minutes of a movie and then not understanding fully what is happening in the movie later on.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the English meaning of those programming terms may not negatively affect their thinking. On the contrary, knowing the meaning of the English terms may significantly improve their learning of computer programming (Qian & Lehman, 2016). Therefore, when teaching computer programming to Chinese students, it is important to stress the meaning of the English-based programming commands to help them understand programming concepts.…”
Section: Student Misconceptions In Computer Sciencementioning
confidence: 99%
“…There are also discussions by some researchers in the gender gap between males and females in the field of computing, particularly information technology (13)(14)(15)(16) . A limited study has showed that male students have a higher ability in programming class than female students (17,18) .…”
Section: Introductionmentioning
confidence: 99%